920 Long Term Outcomes After Resection of A 'Normal' Appendix. (4th May 2021) - Hammett, F; Ali, S; Adair, R; Peter, M; Dobbins, B; Saha, A
Abstract: Introduction: Recent studies have suggested that there should be diagnostic confirmation of appendicitis prior to surgical resection to reduce the rate of negative (normal) appendicectomy. There are few long-term analyses of morbidity after negative appendicectomy. Method: All appendicectomy specimens removed for suspected appendicitis from June 2010 to August 2015 at a single-centre surgical unit were identified. Patients with a histologically 'normal' appendix were analysed. Demographics, pre-operative and operative details and post-operative outcomes (Clavien-Dindo system) were recorded. Minimum follow-up was 5 years. Results: There were 1977 patients. Most (1938 patients, 98%) had a laparoscopic procedure. There were 241 normal specimens (12.1%); none of these patients had pre-operative CT imaging. Thirty-two patients had at least one re-admission in the 5 years after surgery; 12 of these patients had multiple re-admissions (range, 2-5 re-admissions). 22 patients (69%) had a re-admission within 30 days after primary surgery. 4 patients (<1%) required further surgery and mortality was 0%. 6 patients (2%) had a Grade III complication, and none had a Grade IV complication. Conclusions: There was low long-term morbidity after negative appendicectomy in this study. The cost of confirming a normal diagnosis by way of mandatory pre-operative CT does not represent a cost-effective method of management.